Performance of two new automated assays for measuring von Willebrand activity: HemosIL AcuStar and Innovance - Maistre, Emmanuel de; Volot, Fabienne; Mourey, Guillaume; Aho, Ludwig S.; Ternisien, Catherine; Briquel, Marie-Elisabeth; Bertrand, Marie-Anne; Tardy, Brigitte; Frotscher, Birgit; Nguyen, Philippe; Dumont, Laure; Vandroux, David; Hezard, Nathalie; Trossaërt, Marc (Thrombosis and Haemostasis, 2014)
The ristocetin cofactor activity assay (VWF:RCo) is the reference method for assessing von Willebrand factor (VWF) activity but remains difficult to perform, and the coefficient of variation of the method is high (about 20–30%). This study evaluated and compared the performance for measuring the VWF activity of two newly commercialised assays [VWF:Ac Innovance (VWF:Ac) and VWF:RCo Acustar (VWF:RCo Acu)] with the reference VWF:RCo aggregation in 123 pathological plasma samples. The correlation and concordance between both new tests (VWF:RCo-Acu and VWF:Ac) and the reference VWF:RCo were good. The results of the VWF activity to VWF antigen ratio were also comparable whatever the method for the classification of VWF deficiency in all patients. Our results showed that both new tests could replace the “gold standard” VWF:RCo in aggregometry with several benefits: they are fully automated, easier and faster to perform, better adapted to emergency situations if necessary.
Keywords: Willebrand activity assay; ristocetin cofactor activity; aggregometry; von Willebrand disease